Strategic management: origin, process, approaches and theories - Sulaiman, Mohamed; Hashim, Mohd Khairuddin (Universiti Utara Malaysia, 2003)
Much has been written in the literature about the importance of strategic management in organizations. Regardless of size, organizations are seeking and identifying effective strategies through the strategic management process to assist them in the successful management of their businesses. Not-withstanding the tremendous attraction of strategic management, scant attention has been given to investigate its development to the current level of understanding. Based on the literature, this article examines its origin, process, approaches and theories.